A Comparison between Laparoscopic and Open Pyeloplasty in Patients with Ureteropelvic Junction Obstruction - Simforoosh, Nasser; Basiri, Abbas; Tabibi, Ali; Danesh, Abdolkarim; Sharifi-Aghdas, Farzaneh; Ziaee, Seyed Amir Mohsen; Nooralizadeh, Akbar; Hosseini-Moghadd, Seyed Mohhammad Hossein (Urology Journal, 2009)
Purpose: To compare clinical and radiological outcomes, complications, and hospital stay in laparoscopic and open pyeloplasty. Materials and Methods: From February 2002 to February 2003, 69 patients with ureteropelvic junction obstruction (UPJO) were assigned into two groups. Thirty-seven patients underwent transperitoneal laparoscopic pyeloplasty and 32 underwent open surgical pyeloplasty. Clinical symptoms were assessed before and after surgery, subjectively. Radiological assessment was also done three months postoperatively. Results: Mean operative time was 3.2 hours and 2.2 hours in laparoscopic and open pyeloplasty groups, respectively. Intraoperative bleeding was trivial in both groups and no complication or conversion to open surgery occurred. Postoperative complication rates were 24% and 6% in laparoscopic and open pyeloplasty groups, respectively. Mean hospital stay was similar (6.2 days) in the two groups. Mean follow-up was 16.5 months versus 11.4 months. Clinical and radiological success rates were 89% and 83.8% for laparoscopy group versus 96.5% and 87% for open pyeloplasty group. Due to recurrence of stricture, repeated surgery was performed in 4 patients of laparoscopy and 1 of open pyeloplasty groups. Conclusion: Laparoscopic pyeloplasty is a less invasive method with less pain, cosmetic advantages, no long incision, and outcome comparable with open surgery. Hospital stay is also not longer than that in open surgeries. Hence, laparoscopic pyeloplasty can be a substitute for skilled surgeons.